Library power: a new philosophy of librarianship, de James Thompson - Miranda, Antônio (Revista de Biblioteconomia de Brasília, 1975)
THOMPSON, James. Library power: a new philosophy of librarianship. London: Clive Bingley, 1974. 111 p.